2006
DOI: 10.1183/09031936.06.00127205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three auto-adjusting positive pressure devices in patients with sleep apnoea

Abstract: Auto-adjustable continuous positive airway pressure (APAP) devices are an emerging treatment alternative to fixed-pressure continuous positive airway pressure (CPAP) therapy for obstructive sleep apnoea syndrome. They have been engineered to automatically adjust the pressure to the optimal level on a continuous basis. However, not all APAP technologies use the same algorithm. Three different APAP devices (Autoset Spirit, Breas PV 10i and RemStar Auto) were compared in a randomised crossover trial in patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The authors concluded that, in general, A-CPAP therapy does not offer advantages in the evaluated outcomes over fixed-pressure CPAP and the latter remains the standard for PAP treatment. More recent clinical studies addressing this question (104,(107)(108)(109)(110)(111) have not provided evidence to warrant modification of this conclusion. RCTs are clearly needed to determine whether there are subpopulations of patients with OSAH that would derive outcome and adherence benefit from A-CPAP therapy.…”
Section: Treatment Of Osah With Pap Modalities Other Than Fixed-pressmentioning
confidence: 97%
“…The authors concluded that, in general, A-CPAP therapy does not offer advantages in the evaluated outcomes over fixed-pressure CPAP and the latter remains the standard for PAP treatment. More recent clinical studies addressing this question (104,(107)(108)(109)(110)(111) have not provided evidence to warrant modification of this conclusion. RCTs are clearly needed to determine whether there are subpopulations of patients with OSAH that would derive outcome and adherence benefit from A-CPAP therapy.…”
Section: Treatment Of Osah With Pap Modalities Other Than Fixed-pressmentioning
confidence: 97%
“…Some of these systems can also provide information about the residual apneas or hypopneas while patients are on CPAP (i.e., automated CPAP) ( Figure 1B) [36,37] . Although treatment with automated CPAP improves patient satisfaction and compliance in a subset of patients with obstructive sleep apnea (OSA), the routine use of automated CPAP for OSA treatment provides limited benefit [38][39][40] . Furthermore, although Figure 1 Effects of positive airway pressure on hemodynamics.…”
Section: Cpapmentioning
confidence: 99%
“…Comparative trials of A-CPAP versus F-CPAP, as well as between different A-CPAP devices with respect to compliance and subjective preference, have provided equivocal results. Some studies report similar effects, while others point out significant differences [33,36,[40][41][42][43][45][46][47][48][49][50]. Once again, when differences were found, they were often small and appeared unrelated to delivered pressure levels.…”
Section: Do Different A-cpap Devices Perform Equally?mentioning
confidence: 87%
“…Studies on patients with OSAHS showed that levels and variability of pressure delivered by the A-CPAP devices can be different [32][33][34][35][36], sometimes to a considerable extent. However, despite differences in pressure output the effects on polysomnographic variables prove to be similar for most A-CPAP devices.…”
Section: Do Different A-cpap Devices Perform Equally?mentioning
confidence: 99%